Evaluation of Percutaneous Peritoneal Drainage Among Patients with High Risk Perforated Peritonitis in Tertiary Care Hospitals - Muhammad Qammar Noshad, Umair Ahmad, Atif Iqbal, Manisha Aswani, Aazma Mirza, Muhammad Haider Ali, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: The aim of this study was to evaluate the effectiveness of percutaneous peritoneal drainage (PPD) as a treatment option for high-risk perforated peritonitis in tertiary care hospitals. Methods: This prospective investigation was conducted at multiple centres including Department of Surgery, Quaid-e-Azam Medical College / Bahawal Victoria Hospital Bahawalpur and Jinnah International Hospital, Abbottabad from August, 2022 to January, 2023. Patients with peritonitis accompanied by shock or who did not respond to initial resuscitative protocols were included in the study. Patients with primary peritonitis or spontaneous bacterial peritonitis and those with a history of multiple previous abdominal surgeries were excluded. The study evaluated the effectiveness of PPD as a treatment option for high-risk perforated peritonitis. Chi Square test was applied to assess association keeping P value < 0.05. Results: The mean age was 54.81±9.2 years, male patients were 66 (57.9%) while female patients were 48 (42.1%). Regarding mortality after PPD 25 (21.9%) patients died, while 15 (13.2%) patients died after definitive surgery. Mortality after PPD was significantly associated with systolic BP < 90 mmHg and comorbid. Conclusion: Based on our study findings, we have determined that percutaneous peritoneal drainage is a crucial procedure that can potentially save lives and lead to improved outcomes in high-risk patients undergoing laparotomy. Moreover, it has the potential to enhance their preoperative condition. Keywords: High risk patients, Primary peritoneal drainage, Perforation peritonitis